Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kedisiplinan Kerja Pegawai Pada Kantor Satuan Polisi Pamong Praja Kota Pontianak - Adiyanto Adiyanto; Aprina Kuswardani (STIE Widya Manggala, 2020)
the human resource is a very important asset and a valuable productivity and efficiency should be improved to make it more powerful and able to optimally in achieving the desired results. Police units of teachers ‘ Praja Pontianak town in terms of the Organization’s operational strategy adequate to carry out the tasks and authorities in accordance with the principles and activities of the organization. One of the indicators of the quality of work of employees in an organization or government agency can be seen from the level of observance or discipline employees in your organization or agency. So discipline is the key to the success of a number of agencies in achieving its goals.The purpose of this research is to know the factors that affect the level of discipline of work employees on Police teachers ‘ Praja Pontianak town. The number of samples as many as 40 people. Determination of the number of samples specified with Stratified Random Sampling. This study used multiple Linear regression analysis technique. Simultaneously it can be concluded that the factor is goals and capabilities, exemplary leadership, retribution, justice, waskat, legal sanctions and humanitarian relations significantly influential/real against the level of discipline in the Police officer’s work Teachers ‘ Praja Pontianak Town. It can be concluded that a partially variable goals and capabilities, exemplary leadership, retribution, justice, waskat, legal and humanitarian relations sanctions take effect against the real level of discipline on Police officers working Teachers The Municipal City Of Pontianak.